EFFICACY AND SAFETY OF ANTISCABIETIC AGENTS : A SYSTEMATIC REVIEW (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Scabies is a contagious skin condition that is caused by a mite called Sarcoptes scabiei. This mite burrows into the skin and causes a severe itching sensation. Scabies can be spread either directly from person to person through scratching or indirectly through contact with contaminated surfaces or objects (fomites). Due to the fact that many people may only exhibit mild symptoms, accurate diagnosis of this ailment can be challenging at times. Scabies can be effectively treated with a variety of different medications. However, clinical trials comparing the efficacy of these treatments, in particular the available topical agents, are relatively few in number. As a consequence, prescribing practice varies greatly from country to country and is largely determined by factors such as the cost and availability of treatments as well as the individual preference of the treating physician. Permethrin, oral ivermectin, and synergized pyrethrins appeared to provide the best balance between these two outcomes compared to the other treatments. These three treatments were located closer to the right upper corner of the clustered ranking plot than the other treatments. On the other hand, the fact that the adverse events (AEs) that were reported in these trials were not serious adverse reactions (such as hospitalization or death) means that one could rationally give them less weight than the cure. Our study found that ivermectin and permethrin were the most effective treatments. The antiscabietic agents used in this study had few or manageable adverse effects, and the study did not find any severe adverse effects.